Analisis Kemampuan Pemahaman Matematis Siswa Ditinjau dari Soal TIMSS - Hilya Alfiani; Dani Firmansyah (Universitas Batanghari Jambi, 2022)
This study aims to analyze students' mathematical understanding abilities in terms of indicators on TIMSS questions. The sample of this research consists of secondary data which is a variety of information that has existed before and was deliberately collected by researchers which is used to complement the needs of research data. The research method used is descriptive qualitative. In collecting the data used to process students' mathematical understanding abilities in terms of students' initial abilities, the data from the students' mathematical understanding ability test results from 5 class VIII student respondents who were around the home environment using quota sampling technique. Data analysis used in two stages, namely collecting data on students' mathematical understanding ability test results, then simplifying the collection of the data obtained. From the results of the study, it was found that there were students who were able to understand the questions and could do it correctly, and there were still students who could not understand the questions and were less thorough in working on the questions.